Private lives [videorecording (DVD)] - Franklin, Sidney A., 1893-1972; Shearer, Norma, 1902-1983; Montgomery, Robert, 1904-1981; Denny, Reginald, 1891-1967; Hersholt, Jean, 1886-1956; Merkel, Una, 1903-1986; Coward, Noel, 1899-1973 (Turner Entertainment Co. : Warner Bros. Entertainment : Distributed by Warner Home Video, 2010)
Amanda and Elyot--a witty, sophisticated married couple--divorce and marry other mates. Amanda chooses stuffy Victor, while Elyot's selection is the tiresome Sibyl. Coincidentally, both newlywed couples honeymoon at the same Swiss hotel--in adjoining suites, in fact. Amanda and Elyot realize anew that the flame of their love has never been extinguished, but when both slip off for a lover's tryst, they fall into their old pattern of ceaseless bickering. When Victor and Sibyl catch up with their erring mates, they themselves begin arguing.